Examining the Effect of Green HRM Practices on Green Creativity: The Mediating Role of Green Identity and the Moderating Role of Ecocentric Leadership - Arfan Akbar; Dr.Sajjad Ahmad (Al-Qanṭara, 2024)
As environmental sustainability becomes increasingly important, organizations are turning to Green Human Resource Management (Green HRM) practices to foster eco-friendly behavior. Green HRM practices are believed to enhance green creativity among employees, while green identity can mediate this relationship, and ecocentric leadership may moderate it. However, limited empirical studies have explored these complex relationships in organizational contexts. This study aimed to examine the effect of Green HRM practices on green creativity, considering the mediating role of green identity and the moderating role of ecocentric leadership in organizations actively implementing sustainability initiatives. A quantitative, cross-sectional survey design was employed, targeting employees in industries such as renewable energy, green manufacturing, and eco-focused services. A sample of 500 employees was selected using stratified random sampling from organizations implementing Green HRM practices. Data were collected through a structured questionnaire measuring Green HRM practices, green creativity, green identity, and ecocentric leadership using validated scales. Statistical analysis was performed using SmartPLS 4.0, employing partial least squares structural equation modeling (PLS-SEM) to assess the relationships between the variables, with bootstrapping for mediation analysis and interaction terms for moderation analysis. Preliminary findings indicate that Green HRM practices significantly enhance green creativity, with green identity acting as a mediator. Moreover, ecocentric leadership was found to significantly moderate the relationship between Green HRM practices and green creativity, highlighting the importance of leadership in fostering sustainability-oriented behavior in employees. The study contributes to the understanding of how Green HRM practices influence green creativity and demonstrates the critical roles of green identity and ecocentric leadership. These findings provide valuable insights for organizations aiming to promote sustainable innovation and creativity through strategic HRM initiatives.